Practical lock picking : a physical penetration tester's training guide - Ollam, Deviant (Syngress/Elsevier, 2012)
Practical Lock Picking, 2nd Edition is presented with rich, detailed full-color diagrams and includes easy-to-follow lessons that allow even beginners to acquire the knowledge they need quickly. Everything from straightforward lock picking to quick-entry techniques like shimming, bumping, and bypassing are explained and illustrated. Whether you're being hired to penetrate security or simply trying to harden your own defenses, this book is essential. This edition has been updated to reflect the changing landscape of tools and tactics which have emerged in recent years. Detailed photos make learning as easy as picking a lock DVD is filled with indispensible lock picking videos and color photos. Extensive appendix details tools and toolkits currently available for all your lock picking needs.